STRATEGI GURU DALAM MENGEMBANGKAN KEGIATAN KEAGAMAAN MELALUI KEGIATAN DOA BERGERAK - Ningsih, Nur Fitria; Rozi, Syaikhu; M Syarif (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Teachers not only serve as transmitters of academic content but also play a vital role as moral and ethical guides for students. This study aims to describe and evaluate the strategies implemented by Islamic Religious Education (IRE) teachers in developing religious activities. The background of this study is based on the strategic role of IRE teachers in shaping students’ religious character through well-organized religious activities. This study uses a qualitative approach with a case study method to gain a comprehensive and in-depth understanding of what is happening in the field. This research employs a case study approach, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The findings reveal that the strategy of habituating students to participate in religious activities such as collective prayers conducted by visiting students’ homes has been effectively implemented. This success is supported by the collaboration among teachers, the school, and parents. The strategy has proven to increase student engagement in religious activities and strengthen the development of religious character. The study recommends innovation in the types of activities and improvement in supporting facilities to further optimize students’ spiritual development. This study shows that the strategy of Islamic Education (PAI) teachers in developing religious activities is carried out through the planning and implementation of a joint prayer program. This strategy includes stages of discussion among teachers, program determination by the principal, and structured implementation of activities. The primary objective of these activities is to strengthen students' religious foundations, improve the fluency of reciting istighotsah and tahlil, and seek smoothness ahead of exams. Additionally, these activities serve as a means for the school to introduce itself to the surrounding community, with the primary target being ninth-grade students. The positive impacts of this program include the smooth conduct of exams and good student graduation rates, an increase in the number of new students each year, and improved school image and relations with the community.